An Experimental Determination of Temperature Profile in an Offset-halves Journal Bearing with Different Oils - Amit Chauhan (Japanese Society of Tribologists, 2007)
In the present work, an offset-halves journal bearing with ID=65 mm, OD=85 mm, L=65 mm, Cm=200 μm and C=500 μm has been tested to access temperature rise while operating with oils namely, Mak 2T, Hydrol 68 and Mak Multigrade at loads varying from 100-600 N and speeds from 3000-4000 rpm at constant supply pressure. Flow rates for different conditions were measured directly and the temperature information on three circumferential planes across the width of bearing was collected. The results indicate that with increase in load at constant speed and with increase in speed at constant load, the circumferential temperature of bearing increases in both the lobes for all the oils. For lower lobe, maximum temperature rise in central plane of the bearing is observed as 31.4ºC for Mak Multigrade oil at 4000 rpm and 600 N and minimum temperature rise is observed as 20.9ºC for Mak 2T oil at 3000 rpm and 100 N. For upper lobe, maximum temperature rise in central plane of the bearing is found to be 16.8ºC for Mak Multigrade oil at 4000 rpm and 600 N and minimum temperature rise is found to be 9ºC for Mak 2T oil at 3000 rpm and 100 N. Across the width of bearing, temperature rise is highest for Mak Multigrade oil (17.9ºC at 4000 rpm, 600 N) and is lowest for Mak 2T oil (8.3ºC at 3000 rpm, 100 N). Hence under the chosen operating conditions (load up to 600 N and speed up to 4000 rpm) and the oils, it is appropriate to use Mak 2T oil so as to make the bearing run cool.